Auswirkungen der Markttransparenzstelle für Kraftstoffe - Justus Haucap; Ulrich Heimeshoff; Christiane Kehder; Johannes Odenkirchen; Susanne Thorwarth (Wirtschaftsdienst, 2017)
Im Dezember 2013 wurde die Markttransparenzstelle für Kraftstoffe in Betrieb genommen. Jetzt stellt sich die Frage, ob die Einführung tatsächlich zu einer Intensivierung des Wettbewerbs auf dem Tankstellenmarkt beigetragen hat. Die hier vorgestellte Analyse beruht erstmals auf umfassenden Mengendaten zum Tankverhalten, sodass sich Verhaltensänderungen und die Wirksamkeit der Markttransparenzstelle untersuchen lassen. – – The authors analyse how the market transparency unit for fuels in Germany affects both supplier and consumer behaviour. The number of price changes has increased, mainly due to increasing price cuts, as has the spread between the lowest and the highest price of the day - both indicators of intensified competition. The concern that the introduction of the market transparency unit would facilitate collusion appears not to be warranted. In contrast, competition has intensified and consumers are increasingly making use of the price differences. The analysis also reveals that consumers purchased more gasoline in times of low prices (so-called price valleys) in 2015 than they did in 2012. The change in consumer behaviour is an indicator that at least some drivers tend to use fuel price comparison apps fed by data from the market transparency unit.
Keywords: D40; L13; 330